2015
DOI: 10.1093/jpepsy/jsv050
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Peer Victimization and Physical Health Problems

Abstract: The stress of PV may contribute to adolescents' sleep problems and somatic complaints and has implications for pediatric psychologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 74 publications
6
45
0
7
Order By: Relevance
“…Together with cross-sectional assessments, this likely results in shared method variance, which raises doubt as to whether direct and indirect effects in the studies reviewed here are over-estimated. Well-powered longitudinal studies were not common among the studies reviewed here (but see Barchia and Bussey 2010;Herge et al 2016;Herts et al 2012;Lereya et al 2013;Mamun et al 2013;McLaughlin et al 2009;Moon et al 2012;Rueger and Jenkins 2014;Turner et al 2010); however, such study designs are needed to identify replicable indirect effects of small size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with cross-sectional assessments, this likely results in shared method variance, which raises doubt as to whether direct and indirect effects in the studies reviewed here are over-estimated. Well-powered longitudinal studies were not common among the studies reviewed here (but see Barchia and Bussey 2010;Herge et al 2016;Herts et al 2012;Lereya et al 2013;Mamun et al 2013;McLaughlin et al 2009;Moon et al 2012;Rueger and Jenkins 2014;Turner et al 2010); however, such study designs are needed to identify replicable indirect effects of small size.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Narayanan and Betts (2014) found no support for a mediational role of resilience in the association between victimization and self-efficacy. Finally, Herge et al (2016) found support for mediating roles of depression and anxiety in the prediction of somatic and sleep symptoms and Guarneri-White et al (2015) showed that general depression but not anxious depression or post-traumatic symptoms explained why victimized adolescents tend to experience more health problems like headaches, fatigue, and vomiting.…”
Section: Mediators On Associations Between Peer Victimization and Othmentioning
confidence: 94%
“…Eligible youth also had higher scores on depressive symptoms ( CES-D M = 23.53 vs. 19.98), but this difference was not significant. Of further note, on average, the 108 adolescents who participated in the screening were already significantly more distressed and victimized than adolescents in a community sample (Herge et al, 2016). Compared to community youth, screened adolescents reported higher levels of social anxiety ( SAS-A M = 48.93 vs. 37.65), depressive symptoms ( CES-D M = 21.32 vs. 13.77), and relational ( M = 2.21 vs. 1.63) and reputational PV ( M = 1.93 vs. 1.51) on the R-PEQ (all p’s < .001).…”
Section: Methodsmentioning
confidence: 97%
“…To provide a benchmark for functioning pre- and post-intervention, we compared participants’ scores on multiple measures to those obtained from a large community sample of adolescents of high-school age (Herge, La Greca, & Chan, 2016). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation